Hubungan Karakteristik dan Kecerdasan Spiritual Perawat dengan Pemenuhan Kebutuhan Layanan Spiritual Pasien Rawat Inap - Nurherawati; Emma Rachmawati; Mouhamad Bigwanto (ARKESMAS [Arsip Kesehatan Masyarakat], 2019)
ABSTRACT Nurses in meeting spiritual service needs in patients are influenced by one of the factors namely spiritual intelligence. The purpose of the study was to determine the relationship between characteristics and nurse's spiritual intelligence by fulfilling the inpatient spiritual service needs in Banten Hospital in 2019. The study was conducted in Banten General Hospital in July-August 2019. This research was quantitative with a cross-sectional design by using a questionnaire as a primary data and using Chi-square test as the data analysis. The sample used all nurses in population with total sampling to 71 nurses. The results showed that respondents who fulfilled the needs of spiritual services were not as good as 37 respondents (52.1%). Bivariate results showed variables related to meeting spiritual service needs, namely the level of education (p value = 0.039), length of work (p value =0.042), and nurse spiritual intelligence (p value =0.022). Based on the results of this study it is suggested that there is a need for assistance or special mentors conducted by senior nurses to junior nurses (length of work ≤ 4 years). Because the results of this research prove that nurses who have a new length of work who have the opportunity to meet the needs of spiritual services are not good for patients. Keywords : Nurses, Spiritual Intelligence, Spiritual Service Needs.